1989
DOI: 10.1016/0250-6874(89)87112-4
|View full text |Cite
|
Sign up to set email alerts
|

Process Integration for active polysilicon resonant microstructures

Abstract: Microsensors based on active polysilicon resonant microstructures are attractive because of their wide dynamic range, high sensitivity and frequency shift output. In this paper, we discuss processing issues for integrating electrostaticallydriven and-sensed polysilicon microstructures with on-chip nMOS devices. Surface-micromachining using sacrificial spacer layers is used to obtain released microstructures. A novel feature is the use of rapid thermal annealing (RTA) for strain relief of the ion-implanted, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Hence the dynamic model is less sensitive to thickness errors than the static model. Using a similar technique, elastic modulus measurements have been carried out on annealed polysilicon cantilever beams 43 and on boron-doped, single-crystalline, (HO)-oriented silicon beams. 33 Dynamic modulus measurement using microbridges (doubly supported beams) have been made on polysilicon 41 and on boron-doped (100)-oriented single-crystalline silicon beams.…”
Section: Elasticity Propertiesmentioning
confidence: 99%
“…Hence the dynamic model is less sensitive to thickness errors than the static model. Using a similar technique, elastic modulus measurements have been carried out on annealed polysilicon cantilever beams 43 and on boron-doped, single-crystalline, (HO)-oriented silicon beams. 33 Dynamic modulus measurement using microbridges (doubly supported beams) have been made on polysilicon 41 and on boron-doped (100)-oriented single-crystalline silicon beams.…”
Section: Elasticity Propertiesmentioning
confidence: 99%
“…(3), certain simplifying assumptions are made, e.g., an ideal clamped boundary condition at the fixed end is assumed. In real devices, however, the microcantilever beam flares at the anchor [6] . On the other hand, as shown in Fig.…”
Section: Rs=85kmentioning
confidence: 98%
“…Furnace annealing is commonly employed to reduce the stress, where the wafers are heated to 1,050 for 1 h in nitrogen ambient. Recently, rapid-thermal annealing has also proven effective in reducing the stress in the polysilicon films [82,84] . A PSO layer is deposited before the stress annealing step so that the polysilicon layer, sandwiched by the PSG layers on the top and bottom, will be annealed symmetrically and the stress gradient will be minimized.…”
Section: Fabrication Technologymentioning
confidence: 99%
“…Conventionally, the film is furnace annealed at 1,050 in a nitrogen ambient for an hour. It has been demonstrated that rapid thermal annealing (RTA) can be used to reduced the stress level in the polysilicon film [82,83] . Experiment has shown that RTA at 1,100 for 60 s will reduce the stress level comparable to that achievable by long furnace annealing.…”
Section: Rapid Thermal Processmentioning
confidence: 99%